Special report on emissions scenarios : (Cambridge University Press, 2000)
How will the world's climate change in the coming century? The answer to this question depends on how human societies develop in terms of demographics and economic development, technological change, energy supply and demand, and land use change. The Intergovernmental Panel on Climate Change (IPCC) Special Report on Emissions Scenarios describes new scenarios of the future, and predicts greenhouse gas emissions associated with such developments. The scenarios provide the basis for future assessments of climate change and possible response strategies. This volume is the most comprehensive and state-of-the-art assessment available of greenhouse gas emissions scenarios, and provides invaluable information for industry, policy-makers, environmental organizations, and researchers in global change, technology, engineering and economics.